2012
DOI: 10.1111/j.1469-7998.2012.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Unlike most vipers, female rattlesnakes (Crotalus atrox) continue to hunt and feed throughout pregnancy

Abstract: For various reasons, reduction or cessation of feeding (anorexia) can occur in either sex during periods of reproduction among vertebrates, from cichlids to elephant seals. Anorexia is commonly associated with gestation in snakes. Using radiotelemetry, we investigated the feeding and spatial ecology of a live‐bearing viperid snake, the western diamond‐backed rattlesnakes (Crotalus atrox). Specifically, from 2001 to 2010, we determined the feeding frequency and home range size of adult females (n = 27) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…But recent work on C. atrox at the SMs has demonstrated that while a biennial pattern is typical for females, annual reproduction is not uncommon [22], [23]. The adult sex ratio at SMs appears to be at unity (G.W.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But recent work on C. atrox at the SMs has demonstrated that while a biennial pattern is typical for females, annual reproduction is not uncommon [22], [23]. The adult sex ratio at SMs appears to be at unity (G.W.…”
Section: Methodsmentioning
confidence: 99%
“…Portions of these spatial data for females have been presented elsewhere [23,23]. We performed three different types of spatial analyses to examine relationships between male proximity and parentage: home range size, pairwise home range overlap between all individuals that were radio-tracked for at least one full year, and geographic midpoint comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Viviparous squamates are also capable of storing large energy reserves to avoid starvation as a result of the effects of locomotor impairment on foraging success, or due to the metabolic demands of carrying a litter of offspring (Bonnet et al, ; Gignac and Gregory, ). Ambush‐foraging species in particular may not suffer detrimental effects of viviparity on either predation or foraging success (Schuett et al, ). Viviparous reptiles can also cannibalize non‐viable offspring to quickly recoup energy after reproduction (Lourdais et al, ; Mocino‐Deloya et al, ; Van Dyke et al, ).…”
Section: Phylogenetic Accuracymentioning
confidence: 99%
“…; but see Schuett et al. ); in conjunction with the metabolic demands of gestation, anorexia can lead to post‐parturient emaciation (e.g., Madsen & Shine ). The intense protein catabolism and musculature loss that occurs during pregnancy has been shown to significantly reduce the physical performance of post‐parturient snakes (Lourdais et al.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the physiological costs associated with viviparity, post-parturient females might be either less capable of engaging in or less willing to engage in energetically expensive antipredator behavior. Specifically, a large reduction in mobility and appetite suppression during pregnancy can result in anorexia during the reproductive cycle (Macartney & Gregory 1988;Bonnet et al 1998;Lourdais et al 2002;Crane & Greene 2008;Webber et al 2012; but see Schuett et al 2013); in conjunction with the metabolic demands of gestation, anorexia can lead to post-parturient emaciation (e.g., Madsen & Shine 1993). The intense protein catabolism and musculature loss that occurs during pregnancy has been shown to significantly reduce the physical performance of post-parturient snakes (Lourdais et al 2004), a consequence of which might be a reduction in antipredator behavior until a positive energy state is achieved.…”
Section: Discussionmentioning
confidence: 99%